No Shortage of Profit: Semiconductor firms and the differential effects of chip shortages - Christopher Mouré (The Mint, 2022)
Few will argue with the claim that shortages are socially harmful. Shortages, by definition, imply a lack of something – not enough stuff to go around. A shortage of food implies hunger; a shortage of electricity implies darkness. But are shortages harmful to everyone equally? And if they are not, does this mean that shortages can also be good for some As the US government prepares – via the CHIPS Act—to hand semiconductor firms around 50 billion USD to help solve the ongoing shortage of semiconductors, it seems worth asking how we arrived at this particular shortage, and whether the answers to the above questions can help us avoid such shortages in the future. Over the past year, I looked into the business of semiconductors. Particularly, I examined the historical relationships between chip production, chip prices, shortages, and profits. I made some surprising findings. First, there is a close negative correlation between the expansion of chip production and changes in prices in the US. This means that when production growth slows down, so does the rate at which chip prices fall. Second, among the dominant semiconductor firms, there is a close negative correlation between the rate of new investment and differential profitability. By differential profitability, I mean profitability relative to a benchmark average – in this case, relative to the average profitability of the 500 largest US-listed firms (measured by market value). Third, there is a close relationship between the appearance of a semiconductor shortage and the differential profitability of these large firms. This relationship has two salient characteristics: shortages tend to appear immediately following a period in which dominant firms trail, rather than beat, average profitability; and dominant firms tend to beat average profitability during years in which a shortage appears. In short, not only do dominant semiconductor firms tend to have significantly higher profits during shortages, but the shortages themselves do not appear to occur by accident.
Keywords: P16; O3; E31; 330; capital as power; computers; differential accumulation; inflation; power; profit; semiconductors; technology; sabotage; scarcity; stagflation